A fixação do quantum debeatur na reparação do dano moral e a indenização tarifada - Fontes, Ieda Uema (2009)
The present work tackles the issue of determining the quantum debeatur in moral hazard indemnification lawsuits. It aims at examing how such amounts are fixed pursuant to the Brazilian legal system, what are the controversies in respect of the settling of such amounts and the possible implications in case the Bill of Law 7.124/02 which defines a table of indemnification amounts for moral hazard, specially as regards death is approved. Therefore, in order to examine this issue vertically, a thorough research has been implemented in the Brazilian legal doctrine and jurisprudence, to assess how the concept of moral damage is constructed and more specifically the parameters to define the quantum debeatur. In addition, the legal doctrine and jurisprudence of foreign legislations have also been examined, to investigate how the determination of the quantum is made abroad. In Brazil, there is a lack of consistency in judicial decisions regarding moral damages indemnification lawsuits, with verdicts clearly unequal for similar situations. The conclusion is that, if the table of indemnification amounts contained in Bill of Law 7.124/02 is enacted, its impacts will be against the principle of total compensation and will not eliminate the different decisions existing for similar cases. The application of a table of amounts, if approved, while at the same time shall serve as a guide for judicial decisions, will also be an obstacle to the full compliance of the restitutio in integrum principle